Implementation of the EVOLUSI (English Vocabulary Submission) Innovation Program Towards Bilingual Schools to Build Character Profile of Pancasila Students - Mukhlisin, Mukhlisin; Zainudin, Ahmad; Setiani, Tri (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2022)
Abstract: EVOLUSI Program (English Vocabulary Submission) is the innovation of English program applied for improving vocabulary skill to all the school members as a form of achieving bilingual school. This research used mixed-method research. The data was collected by questionnaire, interview, and documentations. The research participants were 26 teachers and 313 students the seventh and eighth graders of SMP Islam Al-Fahd Jakabaring. The result showed that there were three main benefits in this innovation program: (1) Teachers and students’ confidence in vocabulary skill for all the school members was improved so that bilingual school could be achieved; (2) The literacy in reading interest for teachers and students was raised effectively and productively; (3) Establish the competent students in realizing Pancasila Student Profile.